Ginsenoside Rg1 Alleviates Acute Ulcerative Colitis by Modulating Gut Microbiota and Microbial Tryptophan Metabolism - Cheng, Hao; Liu, Juan; Zhang, Dandan; Wang, Jing; Tan, Yuzhu; Feng, Wuwen; Peng, Cheng (Frontiers in Immunology, 2022)
Ulcerative colitis (UC) is a chronic and recurrent inflammatory disorder in the gastrointestinal tract. Here, we examined the pharmacological effects of ginsenoside Rg1, a natural compound with low bioavailability, on the acute experimental colitis mice induced by dextran sulfate sodium (DSS) and explored underlying mechanisms. Acute UC was induced in C57BL/6 mice by 2.5% DSS for 7 days, meanwhile, 2 mg/10 g b.w. ginsenoside Rg1 was administrated to treat the mice. Body weight, colon length, colon tissue pathology, and colon tissue inflammatory cytokines were assessed. The composition structure of gut microbiota was profiled using 16s rRNA sequencing. Global metabolomic profiling of the feces was performed, and tryptophan and its metabolites in the serum were detected. The results showed that Rg1 significantly ameliorated DSS-induced colonic injury and colonic inflammation. In addition, Rg1 also partly reversed the imbalance of gut microbiota composition caused by DSS. Rg1 intervention can regulate various metabolic pathways of gut microbiota such as valine, leucine, and isoleucine biosynthesis and vitamin B6 metabolism and the most prominent metabolic alteration was tryptophan metabolism. DSS decreased the levels of tryptophan metabolites in the serum, including indole-3-carboxaldehyde, indole-3-lactic acid, 3-indolepropionic acid, and niacinamide and Rg1 can increase the levels of these metabolites. In conclusion, the study discovered that Rg1 can protect the intestinal barrier and alleviate colon inflammation in UC mice, and the underlying mechanism is closely related to the regulation of gut microbiota composition and microbial tryptophan metabolism.